Analisis Kemampuan Representasi Matematis Siswa Pada Materi Lingkaran - Novia Syafitri; Ellianti Ellianti; Dewi Annisa (Universitas Syiah Kuala, 2023)
This research is driven by the significance of representational proficiencies in acquiring mathematical knowledge. The study aimed to examine students' mathematical representational aptitude in the context of circle. A descriptive qualitative approach was employed to fulfill this purpose, and 31 Year 8 students were selected as the research sample. Data was acquired through tests and subsequent interviews. The findings revealed that students' mathematical representational abilities could be classified as very high in visual representation, high in symbolic representation, and medium in verbal representation. The high-ability group of students demonstrated proficiency across all dimensions of representation, namely visual, symbolic, and verbal. The middle-ability group exhibited proficiency in two dimensions of representation, namely visual and symbolic. The low-ability group only demonstrated proficiency in the visual aspect. Various factors influenced students' representational abilities, including challenges in generating geometric depictions, constructing mathematical models, and articulating mathematical concepts orally. Student errors during problem-solving endeavors were attributed to a lack of attentiveness to the given questions, insufficient review of previous material, limitations in problem analysis, and a deficiency in precision and experience when handling representation-related queries. It is hoped that the findings can serve as a reference for educators to enhance students' representational proficiencies.